Concept of Public Opinion and Democracy: Exploring the Relationship between Public Opinion and Democratic Politics (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The political natures of its data and the extent to which it may vitalize democratic politics theoryhave both been neglected at times by public opinion research. Bernard Berelson, president of theAmerican Association for Public Opinion Research, reaffirms the fundamental requirements of ademocratic politics and explains how opinion research can help a democracy to know itself, evaluate itsachievements, and bring its practices closer to its fundamental ideals. As a result of the Elmira study, Mr.Berelson's interest in this subject has grown and is expressed in that study. The term public opinionrefers to the views of the general public that are expressed in an unstructured manner and try to waypublic policy.